Introducing flat rates and increasing personal allowances in the Spanish personal income tax: An analysis in terms of social welfare for the Spanish regions - Laura Varela-Candamio; Jesús López-Rodríguez; Andrés Faí\~na (European Regional Science Association (ERSA), 2013)
The traditional concept of a strict minimum of nontaxable income equal for all taxpayers embedded in most current income-tax systems is the result of a paradox of fiscal egalitarianism. The paper shows that substituting the traditional notion of a strict minimum of nontaxable income for a scheme of increasing personal allowances to meet the amounts of necessary consumption required by the different living standards of the taxpayers generates an income-tax scheme more progressive than the traditional one. In the paper we also show that this alternative proposal for nontaxable incomes generates an after-tax income distribution less unequal (Lorenz dominance) and superior in terms of social welfare (Atkinson, 1970). The paper defines and evaluates this new tax method, which we refer to as Discretionary Income Tax Method (DITM), based on a) a scheme of deductions from the tax base (discretionary income) based on increasing personal allowances (IPAs) which are modeled resorting on the concept of necessary consumption and identified as increasing personal allowances in the tax b) a flat rate scheme equal for all taxpayers. Then, we focus our empirical analysis in the Spanish case, comparing our alternative proposal against the 2006 Spanish Personal Income Tax (SPIT). From this empirical analysis, using the micro-data from the 2006 Spanish Household Budget Survey and the Sample of Taxpayers from the Spanish Institute for Fiscal Studies, we demonstrate that our results are in line with the theoretical predictions arising from the comparison of the two tax methods. Moreover, since Spanish tax is a tax partially assigned to each Spanish region (Autonomous Communities), we repeat the comparison between our proposal and the 2006 Spanish Personal Income Tax from a regional perspective, replacing the different income levels of individuals by GDP per capita of the different Spanish regions. Again, with our proposal, these regions improve their social welfare using DITM as a fiscal tool in the Spanish income tax. Finally, from a fiscal policy point of view, our tax method proposal is simpler and implies much less administrative and managerial cost and therefore governments and fiscal policy authorities should bear in mind these positive elements in designing personal income tax systems. A very promising research avenue along the lines proposed in this paper would be to compare our tax method proposal with the current personal income tax systems in other countries.
Keywords: D31; D63; H24; 330; increasing personal allowances; tax method; necessary consumption; social welfare; progressivity; Lorenz curves